Akumulasi logam berat (Pb dan Cu) pada Akar dan daun mangrove Avicennia marina di Sungai Lamong, Jawa Timur - Hikmah Farda Awaliyah; Defri Yona; Dwi Candra Pratiwi (Depik, 2018)
Abstract.Mangrove ecosystem of Lamong River is located in an area with dense human activities such as industrial, heavy traffic, settlements and harbour activities. These activities could triggered the input of heavy metals, especially Pb and Cu. Mangrove ecosystem can be developed as a control of heavy metal pollution and also as a pollutant trap. In this study, the analysis of heavy metals (Pb and Cu) in water, sediment and mangorves roots and leaves were measured. Theaim of this study was to determine the ability of Avicennia marinas roots and leaves in absorbing heavy metals (Pb and Cu).Samples were obtained and then analysed byAAS(Atomic Absorbsion Spectrofotometer).The result showed that heavy metal concentrationsof Pb were in the range of 0.11 mg/L - 16.87 mg/L and Cu in the range of 0.001 mg/L - 34.84 mg/L.Avicennia marina in the study site was categorized as excluder based on BCF1 and phytoextraction due to TF1.The results of this study indicate that Avicennia marinacan be developed into phytoremidiation agents because theywas able to absorb and transfer heavy metals from the environment to their plant tissues.Keywords:BCF;TF; Avicennia marina; Heavy metal;Lamong RiverAbstrak.Ekosistem mangrove Sungai Lamong terletak di area yang padat aktivitas manusia seperti aktivitas industri, lalu lintas yang padat, pemukiman dan pelabuhan. Hal tersebut memicu masukan logam berat, khususnya Pb dan Cu. Ekosistem mangrove dapat dikembangkan sebagai pengendalian pencemaran logam berat dan dapat juga digunakan sebagaipollutant trap. Pada penelitian ini bertujuanuntuk mengetahui kemampuanAvicennia marinadalam menyerap logam berat Pb dan Cu dari lingkungannya. Sampel dianalisa menggunakan AAS(Atomic Absorbsion Spectrofotometer).Hasil konsentrasi logam berat Pb berkisar antara 0,11 mg/L 16.87 mg/L dan Cu berkisar antara 0,001 mg/L 34,84 mg/L.Avicennia marinadi lokasi penelitian bersifatexcluderkarena nilai BCF1 dan fitoekstraksi karena nilai TF1. Hasil penelitian ini menunjukkan bahwa mangroveAvicennia marinadapat dikembangkan menjadi agen fitoremidiasi karena mampu menyerap dan mentransfer logam berat dari lingkungan ke jaringan tubuh yang lain.Kata kunci:BCF; TF;Avicennia marina; Logam berat; Sungai Lamong